Effects of management system on performances of the Sicilo-Sarde ewes farmed in Northern Tunisia - Moujahed N.; Jounaidi A.; Kayouli C.; Damergi C. (Nutritional and foraging ecology of sheep and goats, 2009)
The performances of the Sicilo-Sarde dairy ewes were measured in two management systems, practised in Northern Tunisia (region of Béja), that differed by the feeding system, the length of suckling period and the mode of weaning. At Ain Chalou farm, 200 ewes were fed on an improved oat silage and a farm-produced concentrate (18.5% CP) and the suckling period was limited to 45 days. During the last 15 days, ewes were milked twice a day and lambs had access to the residual milk. At Gnadil farm 210 ewes grazing oat were supplemented with commercial concentrate (15% CP). Suckling period was extended to 60 days, where a once a day milking was combined to suckling during the 8 last days. During the milking period, 10 individual milk controls were carried out for all the ewes every 21 days. Body weight variations of ewes from lambing to the beginning of milking, and lambs growth from 30 to 70 days were recorded. Improving the feeding system and shortening suckling period improved total milk production (Ain Chalou: 121 l; Gnadil: 105 l, P < 0.01). Losses in ewe's body weight between lambing and the beginning of milking period was lower at Ain Chalou (-37.5 g/day) than at Gnadil farm (-78.6 g/day, P < 0.05). Lamb growth at 30-70 days was higher (P < 0.05) in Ain Chalou than in Gnadil (respectively 115 and 105 g/day). Under both management systems, the 4-year-old ewes had the highest (P < 0.05) milk production than any other age group. Ewes suckling two lambs produced more milk (P < 0.01) than those with singles. It was concluded that in the farms studied, the improvement of the feeding system and the shortening of the suckling period in Sicilo-Sarde breed ewes improved the amount of commercialised milk and lambs growth, and reduced body weight losses in ewes. The main factors affecting milk yield were the age of ewes and the number and the sex of suckled lambs.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)